Cardiometabolic Consequences of Deleting the Regulator of G protein Signaling-2 (Rgs2) From Cells Expressing Agouti-Related Peptide or the ANG (Angiotensin) II Type 1A Receptor in Mice. Issue 12 (19th October 2022) - Ritter, McKenzie L.; Deng, Guorui; Reho, John J.; Deng, Yue; Sapouckey, Sarah A.; Opichka, Megan A.; Balapattabi, Kirthikaa; Wackman, Kelsey K.; Brozoski, Daniel T.; Lu, Ko-Ting; Paradee, William J.; Gibson-Corley, Katherine N.; et al.
Abstract : Background: RGS (regulator of G protein signaling) family members catalyze the termination of G protein signaling cascades. Single nucleotide polymorphisms in the RGS2 gene in humans have been linked to hypertension, preeclampsia, and anxiety disorders. Mice deficient for Rgs2 (Rgs2 Null ) exhibit hypertension, anxiety, and altered adipose development and function. Methods: To study cell-specific functions of RGS2, a novel gene-targeted mouse harboring a conditional allele for the Rgs2 gene ( Rgs2 Flox ) was developed. These mice were bred with mice expressing Cre-recombinase via the Agouti-related peptide locus ( Agrp -Cre) to cause deletion of Rgs2 from all cells expressing Agrp (Rgs2 Agrp-KO ), or a novel transgenic mouse expressing Cre-recombinase via the ANG (angiotensin) type 1A receptor ( Agtr1a / AT1A ) promoter encoded in a bacterial artificial chromosome (BAC-AT1A -Cre) to delete Rgs2 in all Agtr1a -expressing cells ( Rgs2 AT1A-KO ). Results: Whereas Rgs2 Flox, Rgs2 Agrp-KO, and BAC-AT1A -Cre mice exhibited normal growth and survival, Rgs2 AT1A-KO exhibited pre-weaning lethality. Relative to littermates, Rgs2 Agrp-KO exhibited reduced fat gains when maintained on a high fat diet, associated with increased energy expenditure. Similarly, surviving adult Rgs2 AT1A-KO mice also exhibited increased energy expenditure. Surprisingly, given the hypertensive phenotype previously reported for Rgs2 Null mice and evidence supporting a role for RGS2 in terminating AT1A signaling in various cell types, Rgs2 AT1A-KO mice exhibited normal blood pressure, ingestive behaviors, and renal functions, both before and after chronic infusion of ANG (490 ng/kg/min, sc). Conclusions: These results demonstrate the development of a novel mouse with conditional expression of Rgs2 and illustrate the role of Rgs2 within selected cell types for cardiometabolic control.